Pengambilan Keputusan oleh Istri Peternak pada Peternakan Sapi Potong di Kabupaten Banyumas - Marselina, O; Muatip, K; Djatmiko, O E (PETERPAN (Jurnal Peternakan Terapan), 2024)
This research aims to analyze the influence of education, age, and the amount of working hours of wives of beef cattle farmers on decision-making, which includes purchasing livestock and selling cattle. The research was conducted using a survey method. The determination of the sample size of respondents used the Slovin formula with a margin of error of 10%, resulting in a total of 81 respondents. Data analysis was performed using descriptive analysis and Binary Logistic Regression analysis. The results of the descriptive analysis indicate that the majority of wives of beef cattle farmers had completed elementary school education (56%) and junior high school education (21%), were aged between 31 and 64 years (88%), owned fewer than 4 cattle heads (74%), had 1-3 family members (41%), and had a working hours allocation of less than 0.5 hours or less than 30 minutes (41%). Their involvement in decision-making showed that 46% were in the high category, and 54% were in the low category. The results of the Binary Logistic Regression analysis indicate that the level of education has no significant influence on decision-making (0.474), age has no significant influence on the decision-making of the farmer's wives (0.298), the number of cattle ownership has a significant influence on decision-making (0.088), the number of family members has no significant influence on decision-making (0.138), and the amount of working hours has a significant influence on the decision-making of farmer's wives (0.1).